Exposure to common-use pesticides, manganese, lead, and thyroidfunction among pregnant women from the Infants' EnvironmentalHealth (ISA) study, Costa Rica - Corrales-Vargas, Andrea (2021)
Programa Infantes y Salud Ambiental